(3TQM GdebGeGJ GdMQjQjs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG QCjJ GdebGeGJ GdMQjQjI eTMhfI HGdCdaGX GddZhjI hgj CMO GdcJH GdJi Yfi dgG YdeGA GdYQHjI s
(3BNQgG (B:s
(3hNW GdTjH QCSg NGdUI GdShGO hGdHPF GdeJcde HGdaMT jbGd QLd HPF hGeQGI HPjFI hGdQbhH (B: (3GdeQCI GdJi dG jYjT dgG hdO s
(3HYV CdaGX GdMQjQi GdeTQhMI cJH HGdMeQIs
(3cJHgG fGSNGfs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs